Playing it SMART: increasing transfer student and URM undergraduate student success through undergraduate research combined with group support - Shemer, Gidi (Frontiers in Education, 2024)
Increasing retention rates in STEM disciplines has been a primary goal among universities in recent years. Special attention has been given to increase STEM retention among underrepresented populations in those fields. However, one group of students that remains understudied but faces specific challenges is the transfer (TR) student population. TR students, and especially those who transfer from community colleges (CC-TR) in the US, often face academic and mental hurdles, loss of a sense of academic belonging, and adjustment challenges, sometime described as the "transfer shock". Undergraduate research, an experience that has been shown to promote student success, is often not pursued by STEM TR students due to a heavy load in their new 4-year university. We hypothesized that combining summer undergraduate research in STEM labs with intense group activities that focused on group support, development of research-related skills, and promotion of a sense of belonging, would increase rates of research participation after the summer among transfer students. Moreover, we hypothesized that such an intervention would promote student retention and academic success. Our research demonstrates that this intervention, through a summer program in an R1 university, served as a validating experience that increased participation in STEM research after the program, provided the students with academic skills, and improved graduation and STEM retention of TR and URM students. We believe that this intervention may serve as a model to promote student success among transfer and URM students.